“Tranquilo e favorável”: uma análise semiótica da plataforma de ensino hora do ENEM - Farias, Michaella Araujo (2019)
In this research, a lesson is understood as a syncretic text, as it juxtaposes the verbal and non- verbal language, the teacher's body language, the blackboard, the classroom environment among other elements. The corpus is a teaching platform called “ENEM TIME” (HORA DO ENEM). This project is designed for students who will do the National High School Exam (ENEM). The objects of this research are the first language class entitled Enem’s time: the heart of the matter - Portuguese Language 1, and a program that covers another class, which title is Enem’s time: Linguistic Variation, Textual Interpretation and the Portuguese language in comics. The objectives of this research are: 1) to identify the enunciative strategies raised by the multiple narrators, 2) to understand the teacher’s and student’s profiles as well as the content, 3) and how these profiles influence the production of meaning and promote interaction. Thus, we will use the Discursive Semiotics and the concepts developed by Greimas (1979) about the levels of the Generative Path of Signification. In addition to it, to apprehend the fundamental level, we use Fiorin (2000), the works of Barros (2002; 2004) which contribute to the study of narrativity, and to study the third level - the discursive one - we use, in addition to those already mentioned, the postulates of Fiorin (2016) that explains the enunciative categories established by Benveniste (1974). To appreciate the expression plan, we add the perspective of Floch (2009) and Teixeira’ methodological proposal (2009), which is a script for the analysis of verbal-visual texts. The results reveal signs of a search suitability search by the sender towards the receiver, in order to promote an interaction by approximation. The results of the analysis showed that the hosts and teachers act as student’s assistants, the one who is preparing for ENEM. We realized that the enunciation turns to exam literacy, with tips and problem solving. The teacher’s profile shows someone young, modern and bold. The visual expression in the scenery and in the opening sequence also corroborate for a lighthearted teaching, which means without much effort. Knowledge is transmitted in a way that is “peaceful and favorable”, it is an idea based on youth and modernity.